2021
DOI: 10.1016/j.rinp.2021.104731
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of COVID-19 transmission dynamics between healthcare workers and community

Abstract: Corona-virus disease 2019 (COVID-19) is an infectious disease that has affected different groups of humankind such as farmers, soldiers, drivers, educators, students, healthcare workers and many others. The transmission rate of the disease varies from one group to another depending on the contact rate. Healthcare workers are at a high risk of contracting the disease due to the high contact rate with patients. So far, there exists no mathematical model which combines both public control measures (as a parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…For this study we used the approach as that of Masandawa et.al [19] As done by Martcheva, [7] one of the classical first steps here is to replace π " and π ( with its equal from the equilibria equations, that is,…”
Section: Global Stability Of the Monkeypox-virus Endemic Equilibrium ...mentioning
confidence: 99%
“…For this study we used the approach as that of Masandawa et.al [19] As done by Martcheva, [7] one of the classical first steps here is to replace π " and π ( with its equal from the equilibria equations, that is,…”
Section: Global Stability Of the Monkeypox-virus Endemic Equilibrium ...mentioning
confidence: 99%
“…There are a number of mathematical models on COVID-19 pandemic developed from the start of this human disturbing disease [ 8 ]. The author discusses social isolation measures taken by the government in Brazil to fight COVID-19 disease, and also, the protection of health workers was discussed by Masandawa et al [ 9 ]. In their study, Khan et al [ 10 ] discussed on isolation and quarantine as the best ways of fighting COVID-19 disease.…”
Section: Introductionmentioning
confidence: 99%
“…It helps in knowing how many in average one sick person can infect. In regards to COVID-19, one study revealed that to be 6.33 which is the highest value in German during the early outbreak of the disease [14] . One of the study done in Africa evinced the value of to be 2.37 [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models can provide an information which can be useful in suggesting an effective strategy for prediction and prevention of the disease in the population. To date, there are plenty of mathematical models for describing the transmission dynamics of COVID-19 [5] , [13] , [14] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%